Współdziałanie gminy i przedsiębiorców prywatnych w realizacji gminnych przewozów pasażerskich - Popowska, Bożena; Chołodecki, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper investigates the legal aspects of the organization of public transport in municipality gmina in Poland. According to the Act of 16 December 2010 on public transport, each municipality is obligated to plan, organize, and manage transport services in their community. In order to provide an efficient and effective public transport system, municipalities often cooperate with private entrepreneurs. The main objective of the paper is to discuss the legal relations between municipality and private entrepreneurs.The authors demonstrate alegal model of cooperation between municipality and private entrepreneurs in the implementation of the municipal public transport in Poland. The paper shows that private entrepreneurs can notably influence public transport in the communities.
Keywords: gminne przewozy pasażerskie; gmina; przedsiębiorcy prywatni; współdziałanie